2014
DOI: 10.1515/hf-2014-0153
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting alkaline nitrobenzene oxidation: quantitative evaluation of biphenyl structures in cedar wood lignin (Cryptomeria japonica) by a modified nitrobenzene oxidation method

Abstract: A modified alkaline nitrobenzene oxidation (NBO) method was developed to enable the analysis of the biphenyl structures of cedar wood lignin. The most essential point of the process is a modified work-up process in pyridine and a prolonged gas chromatography analysis of the silylated products. By applying this mean to cedar wood meal, a novel biphenyl product, dehydrovanillin-vanillic acid (1-carboxy-1′-formyl-4,4′-dihydroxy-3,3′-dimethoxy-5,5′-biphenyl), was detected together with known products, dehydrodivan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…As shown in Figure 2 and Table 4, the amount of β -5′ linkages was obviously higher than that of other condensed structures ( β -1′, β - β ′). Analysis of 31 P NMR of MWLs also exhibited a high amount of α -O-4′ and 4-O-5′ structures in ginkgo shells lignin, which resulted in the nitrobenzene oxidation products yield of both ginkgo shells being much lower than that in general softwoods [45,46]. Tamai et al [45] pointed out that the total yield of vanillin and vanillic acid of cedar ( Cryptomeria japonica ) under nitrobenzene oxidation was 1.95–1.99 mmol/g-lignin, which is about 17% and 26% higher than that in ML and FZ, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2 and Table 4, the amount of β -5′ linkages was obviously higher than that of other condensed structures ( β -1′, β - β ′). Analysis of 31 P NMR of MWLs also exhibited a high amount of α -O-4′ and 4-O-5′ structures in ginkgo shells lignin, which resulted in the nitrobenzene oxidation products yield of both ginkgo shells being much lower than that in general softwoods [45,46]. Tamai et al [45] pointed out that the total yield of vanillin and vanillic acid of cedar ( Cryptomeria japonica ) under nitrobenzene oxidation was 1.95–1.99 mmol/g-lignin, which is about 17% and 26% higher than that in ML and FZ, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of 31 P NMR of MWLs also exhibited a high amount of α -O-4′ and 4-O-5′ structures in ginkgo shells lignin, which resulted in the nitrobenzene oxidation products yield of both ginkgo shells being much lower than that in general softwoods [45,46]. Tamai et al [45] pointed out that the total yield of vanillin and vanillic acid of cedar ( Cryptomeria japonica ) under nitrobenzene oxidation was 1.95–1.99 mmol/g-lignin, which is about 17% and 26% higher than that in ML and FZ, respectively. The high condensation degree of ginkgo shells lignin may also explain why the MWL yield (17.5% and 15.3% for MWL ML and MWL FZ , respectively) from ginkgo shells is low.…”
Section: Resultsmentioning
confidence: 99%
“…Although the frequency varies based on wood species and determination methods, the 5-5′ frequency (19-27%) of softwood lignin determined by permanganate oxidation, 13 C NMR and UV spectroscopy (Pew 1963;Bose et al 1998;Capanema et al 2004) was still much larger than the 4-O-5′ frequency (4-5%) determined by CuO/NaOH permanganate oxidation (Erickson et al 1973) and thioacidolysis/ 31 P NMR (Smit et al 1997), which is well reviewed and reported by Chang and Jiang (2020). In addition to these methods, the alkaline nitrobenzene oxidation method combined with 1 H NMR spectroscopy or gas chromatography is possible to detect the 5-5′ structure from wood sawdust (Katahira and Nakatsubo 2001;Tamai et al 2015). In this study, using KLs as a branched polymer, the frequency of the 5-5′ linkage in the lignin preparations was determined by a combinational method of alkaline nitrobenzene oxidation and 1 H NMR.…”
Section: Introductionmentioning
confidence: 94%
“…The number of C 6 -C 3 units involved in the biphenyl structure has also been indicated by the product yields of the biphenyl structures in lignin via chemical degradation methods. Assuming that Mw of a lignin unit is 200 g mol −1 , studies have determined this number to be 0.07 per C 6 -C 3 unit in Japanese cedar wood meal by the alkaline nitrobenzene oxidation method (Tamai et al 2015), 0.06 per C 6 -C 3 unit in spruce MWL by the permanganate oxidation method (Parkas et al 2007), and 0.02 per C 6 -C 3 unit in pine wood meals by the thioacidolysis method (Yue et al 2016). Because the yields of the biphenyl-type degradation products are not corrected by any factor such as the conversion factor, these numbers indicate the minimum number of the C 6 -C 3 units involved in the biphenyl structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, six softwood and 15 hardwood species were examined by the alkaline NBO method (Tamai et al 2015) to explore the variation in the content of biphenyl structures in softwood lignins, and to investigate the relationship between biphenyl content and the syringyl/guaiacyl ratio among hardwood lignins.…”
Section: Introductionmentioning
confidence: 99%